A novel Ru–polyethersulfone (PES) catalytic membrane for highly efficient and selective hydrogenation of furfural to furfuryl alcohol. Issue 12 (6th March 2018) - Bagnato, G.; Figoli, A.; Ursino, C.; Galiano, F.; Sanna, A.
Abstract : A novel catalytic Ru–PES membrane has been synthesised, characterised and evaluated for the selective hydrogenation of furfural to furfuryl alcohol. The Ru–PES membrane exhibited an high catalytic activity towards furfuryl alcohol (selectivity >99%) with turnover frequency (TOF) as high as 48 000 h −1 . Abstract : A novel catalytic membrane has been synthesised, characterised and evaluated for the selective hydrogenation of furfural to furfuryl alcohol. Unlike conventional methods, involving high pressure and high H2  : feed ratios, this work proposes an innovative ruthenium based Catalytic Membrane Reactor (CMR) to overcome mass transfer limitations, resulting in low H2 requirements, high catalytic activity and high selectivity towards furfuryl alcohol. A UV-curable hydrophilic anionic monomer acrylic acid was used as a coating material on a commercial PES membrane and subsequently Ru nanoparticles were added. The hydrogenation of furfural was carried out in a customised catalytic membrane reactor under mild conditions: 70 °C and 7 bar, exhibiting high catalytic activity towards furfuryl alcohol (selectivity >99%) with turnover frequency (TOF) as high as 48 000 h −1, 2 orders of magnitude higher than those obtained so far.